Selected elements of life style and health issues of 50+ persons - Głowacka, Maria Danuta; Kwapisz, Urszula; Kwapisz, Urszula; Frankowska, Anna (Polish Journal of Public Health, 2011)
Introduction. Modern society is aging. In Poland people at retirement age more and more often and quite readily reach for medicines and take advantage of not only services that let them stay healthy and in good mental health but also of modern developments and facilities used in everyday life. To stay fit till the very old age it is necessary to care for one’s psychophysical condition, prophylaxis and toattend regular checkups above 50 years of age. All the components of so called healthy lifestyle affect the life quality and fitness. Aim. The aim of the study is to describe the lifestyle of people above 50 years of age as well as their health-promoting habits, and most common diseases typical of the study group. Material and methods. Ninety two people above 50 years of age and living in Poznań were surveyed with an extended direct interview. Such life style components as professional activity, cohabitation with other family members, nutritional habits and regularity thereof, physical activity, health checkups, and concomitant diseases, were tested. Results and conclusions. People above 50 years of age are often professionally active and try to look after their psychophysical condition. Despite the numerous diseases which they suffer, they want as long as possible enjoy good health and be useful for their families. Unfortunately, not always fully aware of how they should proceed to make it happen. The support they give the family should result in their health care from family. Therefore in the opinion of not just the elderly but also families and friends, raising awareness and reminding on a regular basis to perform basic examinations, involving the construction of a healthy diet, and encouraging moderate physical exertion is of great importance. Providing the study group members want stay fit and well till the very old age, they should start to make efforts once they are over 50 years of age.